Protein Delivery to Insect Epithelial Cells In Vivo: Potential Application to Functional Molecular Analysis of Proteins in Butterfly Wing Development - Yugo Nakazato; Joji M. Otaki (BioTech, 2023)
Protein delivery to cells in vivo has great potential for the functional analysis of proteins in nonmodel organisms. In this study, using the butterfly wing system, we investigated a method of protein delivery to insect epithelial cells that allows for easy access, treatment, and observation in real time in vivo. Topical and systemic applications (called the sandwich and injection methods, respectively) were tested. In both methods, green/orange fluorescent proteins (GFP/OFP) were naturally incorporated into intracellular vesicles and occasionally into the cytosol from the apical surface without any delivery reagent. However, the antibodies were not delivered by the sandwich method at all, and were delivered only into vesicles by the injection method. A membrane-lytic peptide, L17E, appeared to slightly improve the delivery of GFP/OFP and antibodies. A novel peptide reagent, ProteoCarry, successfully promoted the delivery of both GFP/OFP and antibodies into the cytosol via both the sandwich and injection methods. These protein delivery results will provide opportunities for the functional molecular analysis of proteins in butterfly wing development, and may offer a new way to deliver proteins into target cells in vivo in nonmodel organisms.